2004
DOI: 10.1016/j.ehj.2004.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous cryoablation versus radiofrequency ablation of the slow pathway for the treatment of atrioventricular nodal re-entrant tachycardia: a prospective randomized pilot study

Abstract: The results of this pilot study indicate that transvenous cryoablation using a 4-mm-tip cryocatheter is associated with a comparable acute success rate but a higher recurrence rate as compared with RF ablation in patients with AVNRT. Potential benefits of cryoablation for ablation of AVNRT need to be determined in a larger multi-centre trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 11 publications
0
54
2
2
Order By: Relevance
“…Finally, the availability of Cryo mapping (only with 4-mm catheters) allows for careful evaluation of AV conduction, especially in cases where transient AV block occurred with RFA. In regard to complications, AVNRT ablation with RF or Cryo catheter has been shown to be a safe procedure with complication rates of 0% to 1.3% [3,[5][6][7][8][9]. Application of cryothermal energy at an anatomic location close to the compact AV node may increase the risk of heart block; however, this was not observed in our analysis.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Finally, the availability of Cryo mapping (only with 4-mm catheters) allows for careful evaluation of AV conduction, especially in cases where transient AV block occurred with RFA. In regard to complications, AVNRT ablation with RF or Cryo catheter has been shown to be a safe procedure with complication rates of 0% to 1.3% [3,[5][6][7][8][9]. Application of cryothermal energy at an anatomic location close to the compact AV node may increase the risk of heart block; however, this was not observed in our analysis.…”
Section: Discussioncontrasting
confidence: 71%
“…Radiofrequency ablation (RFA) and cryothermal ablation (Cryo) have both been employed for this purpose. These two modalities have been evaluated and compared in the treatment of AVNRT in multiple trials [3][4][5][6][7][8][9]. These trials suggested RFA to be more effective with success rate of 91-100% compared to 83-97% with Cryo, making RFA the preferred modality for the adult population.…”
Section: Introductionmentioning
confidence: 96%
“…Cryoadherence during ablation results in fixation of the catheter, and not passively sliding along a larger area, as under RF [30]. This can mean that a more precise mapping, or a larger catheter tip, or further cooling, is necessary to achieve the same effect.…”
Section: Today's Limitations In Cryoablationmentioning
confidence: 96%
“…Disappearance of an AH-jump, termination or non-inducibility of AVNRT is considered to be an identification of abolition or modification of slow pathway conduction, and therefore a potentially successful ablation site. Theoretically, on the basis of these aforementioned characteristics of cryothermy, this should lead to less applications, less tissue damage, and abolish the risk of permanent conduction disturbances [28,30]. As progressive ice formation at the catheter tip causes adherence to the adjacent tissue, ablation can also safely be performed at otherwise unstable catheter positions, or even during tachycardia, without carrying the risk for catheter dislodgement at termination of the tachycardia.…”
Section: A Rationale For Cryoablation?mentioning
confidence: 98%
See 1 more Smart Citation